The male of Ascorhynchus constrictus Stock, 1997 (Arthropoda: Pycnogonida), with further new records of deep-sea pycnogonids from New Caledonia, the Solomon Islands and Vanuatu - Bamber, Roger N (Zootaxa, 2011)
Deep-sea pycnogonid material collected during the N/O Alis Campagnes Norfolk 2 to New Caledonia in 2003 and Salomon 2 to the Solomon Islands in 2004, together with two samples from the BOA0 and BOA1 Campagnes to Vanuatu in 2004–2005, has been analyzed. This includes only the second collection of deep-sea pycnogonids from the Solomon Islands. The material includes 22 specimens from seven species from New Caledonia, taken at depths from 265 to 1150 m, 95 specimens from 14 species from the Solomon islands, at depths from 336 to 1218 m, and two specimens of one species from Vanuatu (864–927 m depth). The first male of Ascorhynchus constrictus is described, including the first description of the anterior legs. A new species of Ascorhynchus is partially described, but not named owing to its incompleteness. Seven of the species are new to the Melanesia region, including a notable range-extension for Colossendeis tasmanica. The local zoogeography of these deep-water species is discussed.